Postharvest control of Botryosphaeria dothidea-induced pear ring rot by Chrysanthemum indicum essential oil: Composition, efficacy, and mechanistic insights - Bin Wang; Sha-Sha Liu; Jia-Ying Wu; Meng-Ran Yu; Yun-Kai Lv; Jian Wang; Li-Juan Wang; Fei Cao (Postharvest Biology and Technology, 2026)

Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Oceanic redox evolution in an early Cambrian intrashelf basin, South China - Yuyue Han; Meng Cheng; Jianbo Chen; Thomas J. Algeo; Bo Ran; Mengchun Cao; Zihu Zhang; Haiyang Wang; Dasheng Zhao; Tao Dong; Feng Wang; Taiping Huang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Elucidating time-resolved salt stress response mode of salt-tolerant microalgae under simulated seawater salinity: Molecular strategies for algal cultivation and bioproducts production - Meng Ma; Bing Guo; Xinhao Gao; Ran Li; Zichao Zhao; Tao Sun; Li Yao (Journal of Environmental Chemical Engineering, 2026)

Evaluating the carbon footprint of multinational enterprises in China: Does the source of FDI matter? - Yang Zhou; Ran Wang; Xiyuan Li; Bo Meng (Ecological Economics, 2026)

ODC1-associated astrocytic urea cycle dysregulation in age-related memory impairment - Mengna Wu; Shengyao Zhang; Xi Zhao; Bingyu Zhang; Guoran Wan; Jie Gui; Meng Zhang; Baoxue Yang; Dilong Chen; Guoli Li; Qiu Chen; Boyue Huang; et al. (Biogerontology, 2026)

Comparative transcriptome analysis identifies ABA/ethylene signaling components and WGCNA hub genes underlying defoliant sensitivity in Gossypium barbadense - Caixia Li; Meng Wang; Zixin Zhou; Zhiqing Liu; Jianping Li; Yaohua Li; Yahui Deng; Yifan Wang; Lingfang Ran; Jiahui Zhu; Alifu Aierxi; Weiran Wang; et al. (Plant Gene, 2026)

A Porous Zn-Salen-Based Organic Ionic Polymer as a Robust Bifunctional Catalyst for CO2 Fixation via Epoxide Cycloaddition - Guo-Ling Li; Rui-Yao Qin; Meng-Meng Wang; Qing Li; Shijian Lu; Jin-Shui Su; Qi Zhang; Yun Zhao; Ran Zhang; Zhong-Hai Ni (Journal of Environmental Chemical Engineering, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

Axial compressive performance of FRP-strengthened reinforced concrete columns in corrosive environment - Ran Feng; Wanshan Li; Wai-Meng Quach; Jun-Jie Zeng (Engineering Structures, 2026)

Asymmetric spectral modulation of bioinspired Janus metafabric toward environment-adaptive thermal and moisture management under extreme conditions - Yang Wu; Long Zhang; Hao-Ran Yang; Jiaqi Li; Yuzhen Hou; Chang-Shun Li; Bobo Shi; Meng Zhou; Wulin Shang; Weiqing Kong; Huan Xu; Gang Zhou; et al. (Chemical Engineering Journal, 2026)

Orbital symmetry matching-mediated synergistic N2/CO2 activation on Cu-Co3O4 for photocatalytic urea synthesis - Meng Qiao; Yan-Fei Mu; Ji-Li Zhou; Su-Xian Yuan; Meng-Ran Zhang; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

Integrated crop-livestock systems: Closing nitrogen cycles to improve nitrogen utilization efficiency in sustainable ruminant production - Guangyou Ran; Gonzalo Cantalapiedra-Hijar; Hieu Nguyen-Ba; Guangyong Zhao; Jun Zhang; Meng M. Li (Agriculture, Ecosystems & Environment, 2026)

Uncovering the climate vulnerability of China’s poverty alleviation frontiers - Feng Zhao; Lijun Zuo; Yuyu Zhou; Liangzhi You; Huabing Huang; Rui Sun; Yuanyuan Zhao; Xunhuan Li; Dawei Zhang; Ran Meng (Global Environmental Change, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Enhanced treatment of high-algae water and membrane fouling mitigation by SPDA@MIL-101-modified polyethersulfone ultrafiltration membranes with magnetic field regulation and magnetic flocculant assistance - Meng Yao; Ang Li; Zhilin Ran; Xiaoqing Dong; Ruiyan Xiang; Ting Chen; Gang Liu (Journal of Environmental Chemical Engineering, 2026)

Establishing PdHg dual-atom sites on defective nitrogen-doped framework activated carbon for effective electrochemical CO2 reduction - Yanlong Gong; Fanfang Meng; Xiaoli Ran; Shixian Xiong; Jiangcheng Li; Xiaohong Yang; Haitao Fu; Xizhong An (Fuel, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Cerebral blood flow alterations in non-auditory tinnitus: implications for cerebral venous congestion pathophysiology - Lu Liu; Milan Jia; Hui Li; Yifan Zhou; Huimin Jiang; Weiyue Zhang; Chenxia Zhou; Jiangang Duan; Ran Meng; Chen Zhou; Xunming Ji (Brain Imaging and Behavior, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Elucidating the molecular mechanism of pancreatic lipase inhibition by small molecules from Auricularia auricula-judae via integrated biophysical approaches - Xia Yin; Hui-Min Li; Jia-Yang Xu; Han Wu; Meng-Yue Dong; Ke-Ran Hao; Jin-Ming Gao (Food Bioscience, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Synthesis, evaluation and preliminary clinical study of novel 68Ga-labeled Nectin-4 targeting PET tracer - Geng Hu; Zexin Xu; Da-Yong Hou; Pengcheng Ran; Liang Cheng; Wei Liu; Yue Zhao; Fan Jia; Xinyue Yang; Huihui You; Baoyuan Li; Hongxin Li; et al. (Chemical Engineering Journal, 2026)

Shimia fortis sp. nov., Isolated from Marine Sediment - Xiao-Yu Dong; Pei-Ran Lin; Xin-Yun Tan; Jia-Qi Li; Zong-Jun Du; Meng-Qi Ye (Current Microbiology, 2026)

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

Associations of urinary environmental phenols with obesity and lipid metabolism in children and adolescents: The expanded Chinese National Human Biomonitoring (CNHBM) project - Nan Jiang; Qi Chen; Beijing Cheng; Ke Meng; Jia Wang; Tianlin Li; Han Chen; Yinghao Liao; Hong Sun; Ran Liu (Environmental Research, 2026)

Regulating surfactant-induced wetting in membrane distillation by counterions - Qinghua Li; Ran An; Jianghao Chang; Yuchuan Meng; Haiqing Chang; Fangshu Qu (Desalination, 2025)

Effect of cooking condiments on swelling and starch-gluten matrix structural/molecular changes of cooked noodles - Wenxin Xie; Peng Wang; Ran Zhao; Kexin Shi; Meng Ma; Yanfei Wang; Qingjie Sun; Man Li; Fengwei Xie (Food Chemistry, 2025)

A comprehensive perspective on intestinal health, physiological status, and growth performance of Larimichthys crocea with different stocking densities in recirculating aquaculture systems - Songpeng Jia; Mengqi Lu; Tianyi Lan; Zhenyu Gao; Ran Meng; Xuelei Wang; Xiongfei Wu; Lin Huang; Xujie Li; Zhongming Zheng; Weiliang Shen (Aquaculture International, 2025)

Mechanism study on chlorobenzene degradation by non-thermal plasma coupled with Mn-Co/HZSM-5 catalyst - Chang Liu; Cuiping Bian; Xiaokai Wang; Chaoyue Meng; Zhenqi Li; Zhoutong Liu; Ran Li; Fenglei Han (Environmental Science and Pollution Research, 2025)

FiVOS: A fish segmentation algorithm based on interactive video object segmentation and filter enhancement - Yuqing Duan; Song Zhang; Shili Zhao; Xiaoyi Gu; Yan Meng; Daoliang Li; Ran Zhao (Computers and Electronics in Agriculture, 2025)

Preliminary study on ameliorative effects of P-Hydroxycinnamic acid on high-fat diet-induced injury in zebrafish - Qianyao Kuang; Delong Meng; Zhen Zhang; Xingyu Chen; Tsegay Teame; Hongwei Yang; Yalin Yang; Chao Ran; Yuanyou Li; Zhigang Zhou (Fish & Shellfish Immunology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Effects of exercise intensity on large yellow croaker (Larimichthys crocea): A comprehensive analysis of growth, physiology, muscle fiber structure, and gut health - Songpeng Jia; Mengqi Lu; Tianyi Lan; Zhenyu Gao; Jie Ding; Ran Meng; Xuelei Wang; Xiongfei Wu; Lin Huang; Xujie Li; Zhongming Zheng; Weiliang Shen (Aquaculture, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Potential role of dietary whole grains in Alzheimer's disease: bioactive components, mechanistic insights, and epidemiological evidence - Meng Shen; Xinru Yu; Suyang Wu; Ju Qiu; Ran Wang; Kai Li; Qian Zhang (Trends in Food Science & Technology, 2025)

Synergistic experimental-numerical investigation of performance optimization and dynamic behavior in perforated electrode electrocoagulation systems for emulsified oil wastewater remediation - Ang Li; Bing Wang; Meng Yao; Zhilin Ran; Zheng Ju; Ting Chen (Process Safety and Environmental Protection, 2025)

Development of a Probe-Based quantitative PCR assay for detecting Nosema bombycis and its application in inspection and quarantine of silkworm egg production - Zhangshuai He; Fangli Xie; Zhuoxi Fan; Yufan Jian; Maoshuang Ran; Yixiang Yu; Ruoheng Zhao; Zhi Zhang; Xueqiang Sun; Mingxin Mu; Tangxin Li; Zhaoyi Guo; et al. (Journal of Invertebrate Pathology, 2025)

Straw is More Effective Than Biochar in Enhancing the Phosphorus Cycle Potential of Saline Soils - Xuewei Guan; Guangming Liu; Rongjiang Yao; Zhaojia Li; Ran Meng; Wei Feng; Xiuping Wang; Jinlin Chen (Journal of Soil Science and Plant Nutrition, 2025)

Probabilistic failure mode-based prediction method for flexural design capacities of precast reinforced concrete and prestressed concrete beams - Yukun Hu; Jitao Yao; Kaikai Cheng; Luyang Zhang; Meng Ran; Hao Li; Jiewei Xu (Bulletin of Earthquake Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A vision foundation model-based method for large-scale forest disturbance mapping using time series Sentinel-1 SAR data - Yuping Tian; Feng Zhao; Ran Meng; Rui Sun; Yuan Zhang; Yanyan Shen; Bin Wang; Jie Liu; Mingze Li (Remote Sensing of Environment, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Active chitosan films crosslinked by vanillin-derived dialdehyde for effective fruit preservation - Ran Li; Zeqi Liu; Juan Guo; Wenbo Xu; Xuan Ning; Xiaojun Li; Meng He; Qingye Liu (Food Hydrocolloids, 2025)

MMFINet: A multimodal fusion network for accurate fish feeding intensity assessment in recirculating aquaculture systems - Xiaoyi Gu; Shili Zhao; Yuqing Duan; Yan Meng; Daoliang Li; Ran Zhao (Computers and Electronics in Agriculture, 2025)

High urea promotes mitochondrial fission and functional impairments in astrocytes inducing anxiety-like behavior in chronic kidney disease mice - Xi Zhao; Shengyao Zhang; Mengna Wu; Binyun Zhang; Guoran Wan; Meng Zhang; Jing Li; Zhuo Fei; Guoqi Zhu; Shaoqiu Jiang; Mohan Xiao; Wanjia Liu; et al. (Metabolic Brain Disease, 2025)

Sonneralignan A, a new lignan from the fruit of mangrove Sonneratia apetala - Yue-Yao Li; Jia-Lang Xia; Meng Bai; Kai Liu; Jin-Hua Wei; Zu-Ran Lv; Yong-Hong Liu; Cheng-Hai Gao; Xiang-Xi Yi (Natural Product Research, 2025)

Manganese on P, N self-doped biochar toward promoting periodate activation for highly efficient tetracycline degradation: Performance and mechanisms - Xiaofang Pan; Hong Ma; Rongning Zhang; Ran Deng; Meng Li; Binfei Yang; Ruiying Zhu; Li Zhao; Yong Liu; Xiaobo Gong (Journal of Environmental Chemical Engineering, 2025)

Polydopamine-functionalized metal-organic framework nanomaterials for enhanced ultrafiltration membrane performance in high-algae water treatment - Meng Yao; Yukun Li; Zhilin Ran; Ting Chen; Zheng Ju (Journal of Environmental Chemical Engineering, 2025)

Study on the dissolved inorganic carbon cycling and carbon emission during the wet season across cascade hydropower stations on the Jinsha River, southwestern China - Dan Zhang; Yufei Bao; Jingjie Feng; Yu Xu; Yuchun Wang; Ran Li; Yanliang Du; Zhuo Chen; Shanze Li; Jie Wen; Meng Sun (Gondwana Research, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Multi-objective optimization design of an umbilical cross-sectional layout based on the sequential least squares quadratic programming algorithm - Qian Ran; Meng Li; Fusen Peng; Yanlian Du; Yijun Shen; Yongqi Ma (Ocean Engineering, 2025)

Comprehensive metabolome and transcriptome analyses shed light on the regulation of SlNF-YA3b in carotenoid biosynthesis in tomato fruit - Peiwen Wang; Siyu Ran; Yuanhang Xu; Fulei Mo; Fengshuo Li; Rui Lv; Fanyue Meng; Huixin Zhang; Yuxin Zou; Lei Yu; Tianyue Yu; Mozhen Cheng; et al. (Postharvest Biology and Technology, 2025)

4-Nitrophenol at environmentally relevant concentrations mediates reproductive toxicity in Caenorhabditis elegans via metabolic disorders-induced estrogen signaling pathway - Jia Wang; Jiechen Yin; Danhong Peng; Xiaoqian Zhang; Zhouhong Shi; Weixi Li; Yingchi Shi; Mingjun Sun; Nan Jiang; Beijing Cheng; Xingchen Meng; Ran Liu (Journal of Environmental Sciences, 2025)

Functional peptide conjugated ordered gold nanoparticles based rational electrochemical immunosensor for highly stable and selective detection of zearalenone - Qingyue Li; Xiya Zhang; Mengtian Chen; Changwei Luo; Ran Yang; Tong Bu; Meng Dang; Xianqing Huang; Lianjun Song; Pingan Zhang; Liang Liu; Yexuan Mao (Food Chemistry, 2025)

Preparation and structural characterization of selenium nanoparticles from Lactobacillus reuteri and their protective effects on DSS-induced ulcerative colitis in mice - Li Sun; Si-meng Liu; Yan Ding; Ran Yang; Hua-jin Zeng (Food Bioscience, 2024)

Hollow and heterojunction-structured Janus nanomotors for pyroelectrodynamic and nanozyme-catalyzed tumor therapy - Jie Meng; Wei Wei; Shuang Xie; Junwu Wei; Zhanlin Zhang; Pan Ran; Xiaohong Li (Chemical Engineering Journal, 2024)

Optimized ammonium-nitrate ratios in constructed wetlands for simultaneously efficient nitrogen removal and greenhouse gas reduction - Ling-Min Zhang; Ran Liu; Xiao-Qin Luo; Ying Liu; Xi-Qi Li; Qing-Jie Meng; Hong-Cheng Wang (Journal of Water Process Engineering, 2024)

Mitigating interfacial recombination enabling efficient semitransparent organic photovoltaics - Hailin Yu; Jiayu Wang; Yuanhao Li; Tianyu Liu; Yufei Gong; Cenqi Yan; Qichao Ran; Qun Luo; Zupan Mao; Xin Wei; Lei Meng; Changqi Ma; et al. (Chemical Engineering Journal, 2024)

Charge transfer complex induced confinement effect between organic semiconductor and polymer chains for enhancing high-temperature capacitive energy storage - Tan Zeng; Chao Yuan; Qiao Li; Zhaoyu Ran; Li Meng; Jing Fu; Dongduan Liu; Jinliang He; Qi Li (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Visible carbon emissions vs. invisible value-added: Re-evaluating the emissions responsibility of multinational enterprises in global value chains - Yunfeng Yan; Xiyuan Li; Ran Wang; Bo Meng; Zhongxiu Zhao; Xuemeng Li (Ecological Economics, 2024)

EMS-induced missense mutation in TaCHLI-7D affects leaf color and yield-related traits in wheat - Zixu Wang; Huiyuan Xu; Faxiang Wang; Lingling Sun; Xiangrui Meng; Zhuochun Li; Chang Xie; Huijiao Jiang; Guangshuo Ding; Xinrong Hu; Yuhang Gao; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

In situ acid production by organic matter induced with trace homogeneous Fenton reagent for membrane fouling control - Rui Miao; Haoxue Ran; Yifan Yang; Yanfei Li; Zhuowen Ma; Yongtao Lv; Xiaorong Meng; Miaolu He; Lei Wang (Water Research, 2024)

A self-assembled 3D nanoflowers based nano-ELISA platform for the sensitive detection of pyridaben - He Chen; Li An; Meng Li; Hao Liu; Zhong Jin; Huan Ma; Jingwei Ma; Juan Zhou; Ran Duan; Di Zhang; Xiu Cao; Tieliang Wang; et al. (Food Chemistry, 2024)

Reactive oxygen species (ROS) modulate nitrogen signaling using temporal transcriptome analysis in foxtail millet - Hui-Xin Meng; Yu-Ze Wang; Xin-Li Yao; Xin-Ran Xie; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; Jia-Gang Wang (Plant Molecular Biology, 2024)

Arsenic uptake and biotransformation mechanisms in Dunaliella salina: Insights into physiological and molecular responses - Yimei Xi; Bolei Han; Zefang Meng; Yongbin Li; Xiangfeng Zeng; Fantao Kong; Tingting You; Ran Bi; Shaofeng Wang; Yongfeng Jia (Algal Research, 2024)

Spatial modelling of street-level carbon emissions with multi-source open data: A case study of Guangzhou - Yingsheng Zheng; Wenjie Li; Lu Jiang; Chao Yuan; Te Xiao; Ran Wang; Meng Cai; Haobin Hong (Urban Climate, 2024)

Smart epoxy coating: g-C3N4 nanosheets loaded MOFs for enhanced anti-corrosion and UV resistance - Xiaodan Li; Hongyu Liu; Shiyun Meng; Feng Wang; Ting Mei; Xiongrui Cai; Ya Ran (Chemical Engineering Journal, 2024)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

Core-shell spherical cerium oxide, N-doped carbon dots and copper oxide nanocomposites with oxidase-like activity for colorimetric detection of hexavalent chromiums - Mingzhu Qiu; Peiqing Guo; Xuefang Lei; Yujin Li; Shaohui Li; Ran Meng; Xibin Zhou (Journal of Environmental Chemical Engineering, 2024)

Polyethylene microplastics induced gut microbiota dysbiosis leading to liver injury via the TLR2/NF-κB/NLRP3 pathway in mice - Ran Xu; Jing-wen Cao; Hong-li Lv; Yuan Geng; Meng-yao Guo (Science of The Total Environment, 2024)

Dynamic response mechanism and precursor characteristics of gneiss rockburst under different initial burial depths - Dongqiao Liu; Jie Sun; Wen Meng; Manchao He; Chongyuan Zhang; Ran Li; Binghao Cao (Journal of Mountain Science, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

EGFR-Activated JAK2/STAT3 Pathway Confers Neuroprotection in Spinal Cord Ischemia–Reperfusion Injury: Evidence from High-Throughput Sequencing and Experimental Models - Shijie Lv; Kunchi Zhao; Ran Li; Chunyang Meng; Guangchun Li; Fei Yin (Molecular Neurobiology, 2024)

Genomic selection for hypoxia tolerance in large yellow croaker - Jie Ding; Yibo Zhang; Xujie Li; Jiaying Wang; Xinming Gao; Qiumeng Xiang; Zhenyu Gao; Tianyi Lan; Songpeng Jia; Mengqi Lu; Ran Meng; Xuelei Wang; et al. (Aquaculture, 2024)

Nitrogen source affects non-aeration microalgal-bacterial biofilm growth progression and metabolic function during greywater treatment - Jiake Li; Beibei Wu; Meng Xu; Xuan Han; Yinuo Xing; Yu Zhou; Mengyao Ran; Yun Zhou (Bioresource Technology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Characterization and immune functional analysis of two new type I crustins in the oriental river prawn Macrobrachium nipponense - Hongxia Jiang; Shuaishuai Zhang; Xuewei Liu; Yizheng Li; Huanxin Li; Ran Zhang; Yuhua Li; Meng Zhang; Lei Wang; Miao Yu; Zhigang Qiao; Xuejun Li (Aquaculture, 2023)

In-situ introduction of CePO4 for stabilizing electrocatalytic activity of quasi-MOF with partially missing C≡N skeleton - Shuke Li; Meng Xie; Xiao Zhang; Nana Wang; Ran Wang; Yanchao Xu; Hongjun Lin; Yang Jiao; Jianrong Chen (Chemical Engineering Journal, 2023)

Urbanization reduces soil microbial network complexity and stability in the megacity of Shanghai - Lan Liu; Zhaochen Zhang; Xin Wang; Ran Zhang; Meng Wang; Nina Wurzburger; Junxiang Li; Jian Zhang (Science of The Total Environment, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Clinical and molecular epidemiologic features of enterovirus D68 infection in children with acute lower respiratory tract infection in China - Qi Li; Xiangpeng Chen; Junhong Ai; Lei Li; Changchong Li; Yun Zhu; Ran Wang; Yali Duan; Meng Zhang; Zhengde Xie (Archives of Virology, 2023)

Effects of dietary disodium fumarate supplementation on muscle quality, chemical composition, oxidative stress and lipid metabolism of Hu sheep induced by high concentrate diet - Meijuan Meng; Xuerui Li; Ran Huo; Guangjun Chang; Xiangzhen Shen (Meat Science, 2023)

Changes in biochemical metabolites in manila clam after a temporary culture with high-quality microalgal feed mixed with the dinoflagellate species Karlodinium veneficum and K. zhouanum - Yuanbo Pan; Ran Meng; Yanrong Li; Ling Yang; Limin Mei; Yanhua Wu; Jilin Xu; Chengxu Zhou; Xiaojun Yan (Harmful Algae, 2023)

Natural restoration enhances soil multitrophic network complexity and ecosystem functions in the Loess Plateau - Jia He; Junhong Zhang; Jianyu Wang; Zhenghong Dong; Zexin Meng; Ran Xu; Yongbiao Ji; Yuyu Li; Jun Chen; Xuyang Qi; Xinsheng Wang; Xiuting Li; et al. (CATENA, 2023)

Remote estimation of leaf water concentration in winter wheat under different nitrogen treatments and plant growth stages - Li He; Meng-Ran Liu; Shao-Hua Zhang; Han-Wen Guan; Chen-Yang Wang; Wei Feng; Tian-Cai Guo (Precision Agriculture, 2023)

NLRP7 participates in the human subcortical maternal complex and its variants cause female infertility characterized by early embryo arrest - Jian Han; Nana Zhang; Qiqi Cao; Xiaodan Shi; Congjing Wang; Ximan Rui; Jie Ding; Chun Zhao; Junqiang Zhang; Xiufeng Ling; Hong Li; Yichun Guan; et al. (Journal of Molecular Medicine, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Selenium Deficiency Leads to Reduced Skeletal Muscle Cell Differentiation by Oxidative Stress in Mice - Bo-wen Bao; Zibo Kang; Yu Zhang; Kan Li; Ran Xu; Meng-yao Guo (Biological Trace Element Research, 2023)

Exploring the PAHs dissipation and indigenous bacteria response in soil amended with two different microbial inoculants - Beibei Wang; Ying Teng; Ran Li; Ke Meng; Yongfeng Xu; Shiliang Liu; Yongming Luo (Science of The Total Environment, 2023)

Persistent luminescence-activated Janus nanomotors with integration of photodynamic and photothermal cancer therapies - Zhanlin Zhang; Tian Xia; Pan Ran; Junwu Wei; Jie Meng; Guiyuan Zhang; Xiaohong Li (Chemical Engineering Journal, 2023)

Effects of soil and water conservation measures on sediment delivery processes in a hilly and gully watershed - Yi Zeng; Xiangdong Meng; Bing Wang; Mengjie Li; Dan Chen; Lishan Ran; Nufang Fang; Lingshan Ni; Zhihua Shi (Journal of Hydrology, 2023)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Mycotoxin surveillance on wheats in Shandong province, China, reveals non-negligible probabilistic health risk of chronic gastrointestinal diseases posed by deoxynivalenol - Fenghua Li; Xinglan Duan; Liwen Zhang; Dafeng Jiang; Xianqi Zhao; En Meng; Ran Yi; Chang Liu; Yirui Li; Jia-Sheng Wang; Xiulan Zhao; Wei Li; et al. (Environmental Science and Pollution Research, 2022)

Whole-transcriptome sequencing identifies key mRNAs, miRNAs, lncRNAs, and circRNAs associated with unexplained recurrent pregnancy loss - Yan Wang; Qing Cheng; Zhengyi Xia; Ran Zhou; Yiming Li; Lulu Meng; Qing Xu; Jianxin Tan; Zhengfeng Xu (Cell and Tissue Research, 2022)

Mechanisms and Stabilization Measures of Layered Slope: A Study Case of a Layered Slope in Sichuan, China - Tao Ran; Zhiquan Huang; Lingchao Meng; Chuang Wang; Xiaolong Li (Geotechnical and Geological Engineering, 2022)

GNSS-based orbit determination method and flight performance for geostationary satellites - Meng Wang; Tao Shan; Min Li; Lei Liu; Ran Tao (Journal of Geodesy, 2021)

Population origin, maternal effects, and hydric conditions during incubation determine embryonic and offspring survival in a desert-dwelling lizard - Yang Wang; Shu-Ran Li; Meng-Yuan Pei; Dan-Yang Wu; Wei-Guo Du (Oecologia, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Complete mitochondrial genome of Atractomorpha sagittaris (Orthoptera: Pyrgomorphidae) and its phylogenetic analysis for Acrididea - Ran Li; Xiaohan Shu; Wei-an Deng; Ling Meng; Baoping Li (Biologia, 2020)

Annual 30-m land use/land cover maps of China for 1980–2015 from the integration of AVHRR, MODIS and Landsat data using the BFAST algorithm - Yidi Xu; Le Yu; Dailiang Peng; Jiyao Zhao; Yuqi Cheng; Xiaoxuan Liu; Wei Li; Ran Meng; Xinliang Xu; Peng Gong (Science China Earth Sciences, 2020)

Characterization and differential expression of microRNA in the freshwater shrimp ( Neocaridina heteropoda ) with different body length - Ran Li; Xin Wang; Qinghao Meng; Liqi Ren; Jieyang Weng; Shen Wang; Jinsheng Sun (Invertebrate Reproduction & Development, 2020)

Seasonal variation in the groundwater dependency of two dominant woody species in a desert region of Central Asia - Xue Wu; Xin-Jun Zheng; Xin-Wei Yin; Yue-Meng Yue; Ran Liu; Gui-Qing Xu; Yan Li (Plant and Soil, 2019)

Differential Transcriptomic and Metabolomic Responses in the Liver of Nile Tilapia (Oreochromis niloticus) Exposed to Acute Ammonia - Zong Xian Zhu; Dan Li Jiang; Bi Jun Li; Hui Qin; Zi Ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Analysis of status and countermeasures of cancer incidence and mortality in China - Chunchun Wu; Mengna Li; Hanbing Meng; Yukun Liu; Weihong Niu; Yao Zhou; Ran Zhao; Yumei Duan; Zhaoyang Zeng; Xiaoling Li; Guiyuan Li; Wei Xiong; et al. (Science China Life Sciences, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

A genome-wide association study on growth traits in orange-spotted grouper (Epinephelus coioides) with RAD-seq genotyping - Hui Yu; Xinxin You; Jia Li; Xinhui Zhang; Shuai Zhang; Shoujia Jiang; Xueqiang Lin; Hao-Ran Lin; Zining Meng; Qiong Shi (Science China Life Sciences, 2018)

A novel missense mutation of $$ADAR1$$ ADAR 1 gene in a Chinese family leading to dyschromatosis symmetrica hereditaria and literature review - Shuai-Mei Liu; Meng-Xia Ni; Ming-Chao Zhang; Pei-Ran Zhu; Qiu-Yu Wu; Wei-Jun Jiang; Jing Zhang; Wei-Wei Li; Xin-Yi Xia (Journal of Genetics, 2017)

Subliminal trauma reminders impact neural processing of cognitive control in adults with developmental earthquake trauma: a preliminary report - Xue Du; Yu Li; Qian Ran; Pilyoung Kim; Barbara L. Ganzel; GuangSheng Liang; Lei Hao; Qinglin Zhang; Huaqing Meng; Jiang Qiu (Experimental Brain Research, 2016)

Procalcitonin levels in patients with positive blood culture, positive body fluid culture, sepsis, and severe sepsis: a cross-sectional study - Ying Yu; Xia-Xi Li; Ling-Xiao Jiang; Meng Du; Zhan-Guo Liu; Zhong-Ran Cen; Hua Wang; Zhen-Hui Guo; Ping Chang (Infectious Diseases, 2016)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

Polybrominated diphenyl ethers in background surface soils from the Yangtze River Delta (YRD), China: occurrence, sources, and inventory - Yan-Ping Duan; Xiang-Zhou Meng; Chao Yang; Zhao-Yu Pan; Ling Chen; Ran Yu; Feng-Ting Li (Environmental Science and Pollution Research, 2010)

Arsenic trioxide promotes mitochondrial DNA mutation and cell apoptosis in primary APL cells and NB4 cell line - Ran Meng; Jin Zhou; Meng Sui; ZhiYong Li; GuoSheng Feng; BaoFeng Yang (Science China Life Sciences, 2010)

Functional recombinant human anti-HAV antibody expressed in milk of transgenic mice - Ran Zhang; Man Rao; Chuan Li; Jingyuan Cao; Qinglin Meng; Min Zheng; Meili Wang; Yunping Dai; Mifang Liang; Ning Li (Transgenic Research, 2009)

Establishment of a simple and efficient system for somatic embryo induction via ovule culture in Arabidopsis thaliana - Jun Wei; Xin-Ran Li; Meng-Xiang Sun (Plant Cell Reports, 2006)